If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8p + -7p = -6 + 9 Combine like terms: 8p + -7p = 1p 1p = -6 + 9 Combine like terms: -6 + 9 = 3 1p = 3 Solving 1p = 3 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Divide each side by '1'. p = 3 Simplifying p = 3
| -(-2x+4)-2x=4x-20 | | 6(2h-1)+13=19 | | 29=5+3(b+7) | | x-30=6 | | 1/5(-10k+75)=7+15k | | 8=t+1 | | -6x^2=-11x+15 | | (r^2+r-1)(r^2+6r-8)=0 | | 2/3k+1k/4=22 | | 3(x-7)=21 | | 4x+12y=48 | | y=2/3*11/3+1 | | 19=2x-4x+1 | | x+2(x+3)=-9 | | 6(2h-1)+13=9 | | 9m^3n+4m^3n+5mn= | | x=100-4(3)(3) | | 5-2(m+1)=3m-2 | | 3y+30=15+5Y | | 3+1/2x+2/3x+5=41/2 | | (3/4+1/2)/4/7 | | (50x^8+10x^7+x^6)/10x^3 | | S=34t+232 | | -18v+6=10+5t | | -2(a+3)=4a-3 | | v-(5/8)=(-1/2) | | c-5=1-3 | | 2y+34=12+5y | | z+(z-6)=-10 | | 15=9+v/2 | | v-(5/8)=1/2 | | ((81k^-3)^2)/9k^9=0 |